Synthesis, characterization, and multilayer assembly of pH sensitive graphene-polymer nanocomposites - Liu, Jingquan; Tao, Lei; Yang, Wenrong; Li, Dan; Boyer, Cyrille; Wuhrer, Richard; Braet, Filip; Davis, Thomas P (Langmuir, 2010)
pH sensitive graphene-polymer composites have been prepared by the modification of graphene basal planes with pyrene-terminated poly(2-N,N'-(dimethyl amino ethyl acrylate) (PDMAEA) and poly(acrylic acid) (PAA) via pi-pi stacking. The pyrene-terminal PDMAEA and PAA were synthesized using reversible addition-fragmentation chain transfer (RAFT) polymerization with a pyrene-functional RAFT agent. The graphene-polymer composites were found to demonstrate phase transfer behavior between aqueous and organic media at different pH values. Atomic force microscopy (AFM) analysis revealed that the thicknesses of the graphene-polymer sheets were approximately 3.0 nm when prepared using PDMAEA (M(n): 6800 and PDI: 1.12). The surface coverage of polymer chains on the graphene basal plane was calculated to be 5.3 x 10(-11) mol cm(-2) for PDMAEA and 1.3 x 10(-10) mol cm(-2) for PAA. The graphene-polymer composites were successfully characterized using X-ray photoelectron spectroscopy (XPS), attenuated total reflection infrared (ATR-IR) spectroscopy, and thermogravimetric analysis (TGA). Self-assembly of the two oppositely charged graphene-polymer composites afforded layer-by-layer (LbL) structures as evidenced by high-resolution scanning electron microscopy (SEM) and quartz crystal microbalance (QCM) measurements.